ANALISIS PENGARUH PERSEPSI KONSUMEN MENGENAI BAURAN PEMASARAN DAN CITRA MEREK PADA LOYALITAS KONSUMEN MERCEDES-BENZ DI JAKARTA - , Aditya Jamaludin; , Prof. Basu Swastha D., MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to examine the effects of consumers perception about marketing mix (product, price, place, and promotion) and brand image on customer loyalty on Mercedes-Benz in Jakarta. The Hypothesis are marketing mix has a positively significant impact on customer loyalty and brand image has a positively significant impact on customer loyalty. Sample selection is conducted through purposive sampling with conditions, Mercedes-Benz users or ex users who lives in Jakarta. The analysis method to test hypothesis is using kuantittif method. The result showed that individually, product, price, place, promotion, and brand image have a positively significant impact on customer loyalty. But together, only product and distribution that have positively significant impact to customer loyalty.